Trust in generosity: An experiment of the repeated Yes-No game - Werner Güth; Hironori Otsubo (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2014)
This paper reports results of a 100-round Yes-No game experiment conducted under the random matching protocol. In contrast to ultimatum bargaining, the responder in the Yes-No game decides whether to accept without knowing the proposer's offer. Although both games have the same solution outcome (i.e., the proposer offers the smallest possible amount and the responder accepts), the set of equilibria of the ultimatum bargaining game is rather large whereas the equilibrium of the Yes-No game is essentially unique. Avrahami et al. (2013) found an immediate convergence to proposers offering an equal split in their repeated ultimatum bargaining experiment. Our main interest is which dynamics emerge when proposers and responders repeatedly play the Yes-No game. We found neither convergence to offering an equal split nor to the solution outcome. Most participants display a surprising constancy of behavior but the categories of behavior are rather rich.
Keywords: C72; C92; 330; laboratory experiment; learning; repetition; veto power; Yes-No game; Pavitt's sectoral taxonomy